Ebola infection in pregnancy, an ongoing challenge for both the global health expert and the pregnant woman—A review. (March 2021) - Appiah-Sakyi, Kwabena; Mohan, Manoj; Konje, Justin C
Abstract: A new Ebola outbreak is currently ongoing in the Democratic Republic of Congo, after the most severe outbreak in West Africa in 2014–2016 was controlled. Ebola outbreaks are usually a significant cause of death among pregnant women. The clinical presentation of Ebola Virus infection in pregnancy often mimics common pregnancy related bleeding complications or febrile conditions common in pregnancy. The large amount of body fluids discharged during the management of these conditions make pregnancy a highly risky intervention for nosocomial infection transmission, especially to health workers. In this review, we discuss the Ebola virus, its pathogenesis, clinical features, diagnosis and the current supportive intensive medical and obstetric- specific practices to ensure safe management of Ebola positive pregnant women. We present how Ebola may be managed in highly resourced settings where experience is limited in the management of pregnancy complicated by Ebola infection and how wherever these patients are managed, postpartum contraceptive support is necessary because of lingering concerns about sexual transmission. Wider issues highlighted by the Ebola outbreaks included the demonstration of how weak health systems from prolonged lack of investment, in the face of highly infectious diseases like Ebola Virus infection, can pose a risk to the global community, bringing sharply into focus the need for essential collaboration between national health departments and international health organizations such as the World Health Organization.